Trace element bias in the use of CO2 vents as analogues for low pH environments: Implications for contamination levels in acidified oceans - VIZZINI, Salvatrice; DI LEONARDO, Rossella; COSTA, Valentina; TRAMATI, Cecilia Doriana; LUZZU, Filippo; MAZZOLA, Antonio (Estuarine, Coastal and Shelf Science, 2013)
Research into the effects of ocean acidification on marine ecosystems has increasingly focused on natural CO2 vents, although their intrinsic environmental complexity means observations from these areas may not relate exclusively to pH gradients. In order to assess trace element levels and distribution in the Levante Bay (Vulcano Island, NE Sicily, Italy) and its suitability for studying biological effects of pH decline, Ba, Fe and trace elements (As, Cd, Co, Cr, Cu, Hg, Mn, Mo, Ni, Pb, V and Zn) in sediment were analysed from 7 transects.Where present, Cymodocea nodosa leaves and epiphytes were also analysed. At the spatial scale of the bay, trace element concentrations in sediments and biota showed wide variability, possibly related to both input from fluid emissions and seawater physico-chemical variables (i.e. pH and Eh), which may considerably affect the solubility and bioavailability of potentially harmful trace ele- ments. According to two pollution indices (MSPI: Marine Sediment Pollution Index and SQG-Q: Sediment Quality Guideline Quotient), the bay can be considered to be affected by low contamination with moderate potential for adverse biological effects, especially in the area between about 150 and 350 m from the primary vent, where localized detrimental effects on biota may occur. Generally, biological samples showed concentrations that were comparable with the lower values of seagrass ranges. The overall results of this study support the complex spatial dynamics of trace elements in the CO2 vent studied, which are constrained by both direct input from the vent and/or biogeochemical processes affecting element precipitation at the sedimenteseawater interface. Consequently, great caution should be used when relating biological changes along pH gradients to the unifactorial effect of pH only, as interactions with concurrent, multiple stressors, including trace element enrichments, may occur. This finding has implications for the use of CO2 vents as analogues in ocean acidification research. They ...